Identity experiments in two female photographers of Yemeni women - Bokir, Shada Salem; Ruzy Suliza Hashim,; Anita Harris Satkunananthan,; Olmedo, Eric (Penerbit Universiti Kebangsaan Malaysia, 2020)
Boushra Al-Mutawakkil and Amira Alsharifare two of the most importantYemeni photographers; they are both pioneers in presenting facets of Yemeni women through photography. Their works are considered controversial because they present bold and challenging opinions concerning social taboos against women in terms of space of freedom and veiling. Dress codes in Yemen have always been a very sensitive topic for discussion since they are generally linked to religious roots and customary traditions. Through their photographs, Al-Mutawakkil and Alsharif attempt to show the changes in hijab-wearing that range from the elegant traditional Yemeni veil with its diverse designs to the monochromatic abaya, always black and shapeless, a costume imported from the Gulf countries where women’s individual identities slowly disappear. By sharply contrasting the traditional Yemeni costume, the black abaya, and various stages of veiling as women become increasingly invisible as they are shrouded in black, Al-Mutawakkiland Alsharif express the determination, beauty, mystery, significance, danger, and fear as Yemeni women’s identitiesare regulated by politics, religion and culture. This papertherefore highlights Al-Mutawakkil and Al-sharif’s “identity experiments” as they produce scenarios of veiling in deliberately arranged settings as well as in natural public life. The implications of this study towards society are in the dissection of the male gaze in Yemeni society as well as a non-exotic representation of the hijaband how this influences the female identity in conservative Yemeni society.